2016
DOI: 10.1021/acs.molpharmaceut.6b00096
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Formulation and in Vitro Performance Testing of Instantly Disintegrating Buccal Tablets for the Emergency Delivery of Naloxone

Abstract: The aim of this study was to develop a freeze-dried buccal tablet for the rapid delivery of naloxone in opioid overdose. The tablet composition was optimized to produce an amorphous matrix, which was confirmed by the absence of peaks associated with crystallinity observed by differential scanning calorimetry and powder X-ray diffraction. Tablets with high gelatin content lacked adequate porosity. Mannitol was added to the formulation to bridge and intercalate gelatin's tight polymer aggregates, however sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…As mentioned earlier, CSP7 trifluoroacetate formulations were prepared in DPBS buffer, which consists of sodium chloride (NaCl), potassium chloride (KC1), dibasic sodium hydrogen phosphate dihydrate (Na2HP04 2H 2 0) and monobasic potassium phosphate (KH2PO4). There are various studies reporting the effects of buffer salts on crystallinity of the bulking agents, such as delayed lactose crystallization, polymorphic behavior of mannitol, or inhibition of mannitol crystallization (5962). …”
Section: Resultsmentioning
confidence: 99%
“…As mentioned earlier, CSP7 trifluoroacetate formulations were prepared in DPBS buffer, which consists of sodium chloride (NaCl), potassium chloride (KC1), dibasic sodium hydrogen phosphate dihydrate (Na2HP04 2H 2 0) and monobasic potassium phosphate (KH2PO4). There are various studies reporting the effects of buffer salts on crystallinity of the bulking agents, such as delayed lactose crystallization, polymorphic behavior of mannitol, or inhibition of mannitol crystallization (5962). …”
Section: Resultsmentioning
confidence: 99%
“…The interest in an intranasal product supports the recent FDA approval of an intranasal product (Narcan ™ ; Adapt Pharmaceuticals) (Traynor, 2016), which is a commercially available intranasal product that does not require application of an atomizer to an injection ampule to administer intranasally. While Narcan ™ is the only currently FDA-approved intranasal product, a recent international patent search identified patents for new intranasal and sublingual formulations of naloxone (McDonald et al, 2017), and recently published studies have reported the pharmacokinetics of new intranasal (Gufford et al, 2017; Mundin et al, 2017; Tylleskar et al, 2017) and buccal products (Alqurshi et al, 2016), indicating substantial interest in development of noninjected naloxone formulations.…”
Section: Discussionmentioning
confidence: 99%
“…The commonly used instruments used to study the thermodynamic properties are DSC (PerkinElmer Inc.,), DSC-2010 (TA instruments) and Shimadzu DSC-60 plus. The analysis is performed by taking 4-6 mg, of indium pan and heating with temperature gradient depending on melting temperature under nitrogen or argon flow [96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112].…”
Section: Thermoanalytical Methodsmentioning
confidence: 99%
“…Normally the dissolution time depends on the composition of the hard boiled lozenges and it varies from 6 to 10 min. Further human panel can be used to determine the actual dissolution time of the hard boiled lozenges [11,109].…”
Section: Mouth Dissolving Timementioning
confidence: 99%